2008
DOI: 10.1002/pssb.200879596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humidity on the hysteresis of single walled carbon nanotube field‐effect transistors

Abstract: Single walled carbon nanotube field‐effect transistors (SWCNT FETs) are attributed as possible building blocks for future molecular electronics. But often these transistors seem to randomly display hysteresis in their transfer characteristics. One reason for this is suggested to be water molecules adsorbed to the surface of the gate dielectric. In this study we investigate the hysteresis of SWCNT FETs at different relative humidities. We find that SWCNT FETs having atomic layer deposited (ALD) HfO2 – TiO2 – Hf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 25 publications
5
24
0
Order By: Relevance
“…When suspended CNT FETs were exposed to an ambient environment, hysteresis was observed in the current (Ids) versus gate voltage (Vg) characteristics when Vg was swept between -3 V to 3 V [19]. The hysteresis was advancing in nature, and its width (which is defined as the difference in the threshold gate voltages between the down and the up sweep directions) exhibited a strong dependence on ambient humidity, as was previously reported [13,20]. The hysteresis width has also exhibited exponential time dependence on the scanning time of a single sweep period with time constant of τ = 38 ± 4.2 sec (see Fig.…”
Section: Resultssupporting
confidence: 61%
“…When suspended CNT FETs were exposed to an ambient environment, hysteresis was observed in the current (Ids) versus gate voltage (Vg) characteristics when Vg was swept between -3 V to 3 V [19]. The hysteresis was advancing in nature, and its width (which is defined as the difference in the threshold gate voltages between the down and the up sweep directions) exhibited a strong dependence on ambient humidity, as was previously reported [13,20]. The hysteresis width has also exhibited exponential time dependence on the scanning time of a single sweep period with time constant of τ = 38 ± 4.2 sec (see Fig.…”
Section: Resultssupporting
confidence: 61%
“…This observation is in agreement with previous findings, which have reported that humidity affects hysteresis significantly. [26][27][28] Similar curves to those depicted in Fig. 7 were found when the gate bias was swept back from À2 V to zero.…”
Section: Fig 3 @Fsupporting
confidence: 74%
“…I–V curves measured statically under different atmosphere with relative humidity (RH) gradient clearly show a huge decrease in the slope from low RH to high RH at 25 °C. As a humidity sensor, the maximum sensitivity (defined as R RH /R dry ) of the as‐established device can reach as high as 30, which well surpasses the humidity sensing performance of carbon nanotubes 25. Also, the response and recovering time (under stimulus of 90% RH) of our moisture detectors are only 30–40 s and 12–50 s, respectively, which are well shorter than the previously reported SnO 2 nanowire humidity sensor (120–170 and 20–60 s) 26.…”
mentioning
confidence: 99%